2016
DOI: 10.3928/19382359-20160912-01
|View full text |Cite
|
Sign up to set email alerts
|

A Mindfulness Intervention for Residents: Relevance for Pediatricians

Abstract: Physician burnout is a topic of growing importance in today's health care system. Tangible interventions aimed at reducing burnout and promoting wellness are now necessary components of medical training and practice. A study examined the feasibility and impact of a brief mindfulness intervention using a free smartphone application with a resident population. Participants used a free smartphone application to complete a 10-day program in mindfulness meditation, and completed surveys at the end of the program. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 16 publications
4
79
0
Order By: Relevance
“…In all but one study, participation in the MBI was voluntary and based on self‐selection. Response rates for survey completion were between 75% and 100% in seven studies, between 50% and 74% in three studies, and below 50% (or were not reported) in 14 studies . Eight were multicentre studies .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In all but one study, participation in the MBI was voluntary and based on self‐selection. Response rates for survey completion were between 75% and 100% in seven studies, between 50% and 74% in three studies, and below 50% (or were not reported) in 14 studies . Eight were multicentre studies .…”
Section: Resultsmentioning
confidence: 89%
“…Scores for the quality of the studies ranged between 6.5 and 14.5 on the MERSQI scale; the mean score was 9.9, reflecting average quality (Table S2) . The eligible studies included seven randomised controlled trials (RCTs), three non‐randomised controlled trials (CTs), 12 pre‐post studies, and two qualitative interview studies (Table ). Of the RCTs and CTs, four studies employed a waitlist control condition, four studies employed a passive control condition, and two studies exposed controls to protected free time during the intervention period .…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43][44] More feasible interventions, such as 10-20 minute mindfulness meditation for 30 days and a one-hour online module focusing on "mindbody skills training," have also been demonstrated to reduce stress and burnout. [45][46][47][48][49][50][51][52] Mindfulness and self-awareness can be enhanced by journaling, narrative medicine, and reflective questioning, potentially reducing burnout rates, [50][51] although other studies have not shown improvement in burnout. 52 Focused training in behavioral skills, such as cognitive reframing, self-compassion, and empathy, can also improve wellness.…”
Section: Best Practice Recommendations For Assessmentmentioning
confidence: 99%
“…Beyond mindfulness as a concept based on individual experience, the practical implications of mindfulness can enhance the holistic practice of nursing care and the well-being of these workers [9]. Equally, mindfulness in these professionals is an effective strategy for prevention and management of anxiety, stress and exhaustion [10][11][12][13]. At the same time it improves their capacity for regulation and emotional wellbeing, which also has repercussions on the maintenance of successful and satisfactory therapeutic relations with their patients [14].…”
Section: The Importance Of Mindfulness In Nursing Workmentioning
confidence: 99%